Digital education and exercise therapy versus minimal intervention for young people at high risk of early onset knee osteoarthritis after ACL reconstruction: a study protocol for the Stop OsteoARthritis (SOAR) randomized controlled trial - Jackie L. Whittaker; Amanda Cammalleri; Candice Archibald; Alexandra Brooks-Hill; Patrick Chin; Sarah Clark; Jennifer C. Davis; Alison M. Hoens; Michael A. Hunt; Karin Kausky; Angelina Ko; Lise Leveille; et al. (Trials)
Abstract Background People who tear their anterior cruciate ligament and have reconstruction surgery (ACLR) are at elevated risk of inactivity, obesity, and early-onset knee osteoarthritis. Consensus recommendations to prevent post-traumatic knee osteoarthritis include person-centered education and exercise-based treatments. The effectiveness of these recommendations is unknown. This study will assess if a digital education and exercise therapy intervention is superior to minimal intervention for improving knee-related symptoms, function, and quality of life in young people after ACLR. Methods The Stop OsteoARthritis (SOAR) study is a parallel, two-arm, assessor-blinded, superiority, hybrid effectiveness-implementation type 1 randomized controlled trial. After baseline testing, 166 participants aged 16–35 years, 9–36 months past, a first-time ACLR with ongoing symptoms will be randomly allocated to one of two treatment groups (1:1 ratio, stratified by sex). Ongoing symptoms will be defined as not meeting a Patient Acceptable Symptom State (PASS) on the averaged Knee injury and Osteoarthritis Outcome Score pain, symptoms function in sport and recreation, and quality-of-life subscales (KOOS4 < 79). Participants randomized to the experimental intervention will receive a digital (remote videoconferencing) 6-month program of group-based learning, individualized weekly home-based exercise therapy and physical activity program with tracking, and 1:1 physiotherapist-guided counseling. Participants randomized to the minimal intervention control group will receive an educational recording, best-practice guide for ACLR rehabilitation, one videoconferencing session, and tracking. The primary effectiveness outcome is the between-group difference in KOOS4 change from baseline to 6-months, with secondary endpoints at 12- and 24months. Secondary effectiveness outcomes include differences in the change of individual KOOS subscale scores, proportions of participants achieving KOOS subscale PASS scores, perceived self-management, and MRI features of knee OA. We will also assess secondary implementation (perceived barriers and facilitators of SOAR delivery), secondary efficiency (incremental cost-utility ratio), and exploratory outcomes. Missing data will be imputed and blinded intention-to-treat analyses performed. Discussion By assessing the effect, implementation, and efficiency of a digital education and exercise-based intervention designed to improve the knee health of young people at increased risk of knee osteoarthritis, this study will provide a basis for future scale-up to help curb the mounting burden of osteoarthritis. Trial registration ClinicalTrials.gov NCT06195423. Registered on December 22, 2023.